The effects of trade policy on the development of the South African petrochemical industry - Giantsos, John (Rhodes University, Faculty of Commerce, Department of Economics, 1995)
The objective of the research was to determine the role which South African trade policy played in shaping the development of the domestic petrochemical industry. The focus of the study falls on the domestic development of the petrochemical industry in general, and the polymer industry in particular. Three broad stages are distinguished in the domestic development of the petrochemical industry. Prior to the early 1970's development occurred primarily on an ad hoc basis, with the establishment of domestic production plants for most major petrochemicals. The development of the domestic petrochemical industry over the period from the early 1970's to the early 1980's was characterised by rapid growth in the domestic production of petrochemicals, while the period from the early 1980's to the early 1990's saw a significant slowdown in the annual growth rate for the domestic production of petrochemicals. The role of trade policy in the industry's development over each of these three periods could not be established conclusively. In each period a number of factors were identified which may have impacted on the industry's development. However, two factors do appear to have played particularly important roles in the industry's development prior to the early 1980's, namely strong growth in domestic petrochemical demand and the provision of a substantial degree of protection through quantitative import controls and tariffs. with regard to the industry's development over the period from the early 1980's to the early 1990's, a number of factors were identified which may have influenced trends in domestic petrochemical production, including the withdrawal of quantitative import controls and the progressive lowering of import tariffs, the depreciation of the rand in the mid-1980's, a slowdown in the growth of the domestic demand for petrochemicals, the fall in the international prices of petrochemicals in the early 1980's, and the fall in the international oil price in the mid-1980's. In view of the small size of the domestic petrochemical market it is recommended that local petrochemical producers should continue to expand their focus beyond that of producing solely for the requirements of the domestic market. In light of the key role played by the petrochemical industry in a modern economy, it is also recommended that the industry in South Africa receive more attention from policy makers than it has in the past.
Keywords: Petroleum chemicals industry -- South Africa; Petroleum industry and trade -- Government policy -- South Africa; Petroleum chemicals industry; South Africa -- Commerce